The nurse front of the health care of women victims of sexual violence: an integrative review (Research, Society and Development, 2022)
To characterize the role of nursing in health care for women who suffer sexual violence and discuss its performance in the preventive context based on evidence in the scientific literature. Integrative literature review, with a search for primary studies published from 2015 to 2021, carried out in the electronic databases LILACS, MEDLINE, BDENF and IBECS in May and June 2021. The searches were obtained by crossing, in the databases, of the following descriptors and words: “sexual violence”, “nursing”, “nursing care”, correlated and isolated. Eleven articles were included, and the analysis indicated that the evidence available in the literature reports the identification of cases of sexual violence and the performance of care, nurses' perception regarding the approach to women victims of violence and aspects of public policies and the reflection on their Implementation. The role of nursing in care for women victims of sexual violence still presents challenges and the need for adjustments, both on the part of professionals and institutions that offer this type of service. Parallel to this, it is also necessary to advance in the reception of victims, as studies show the magnitude of factors that hinder their access to the health service.